Pengaruh Kompensasi Dan Motivasi Terhadap Kinerja Karyawan (Studi Kasus PT Indoraya Internasional di Yogyakarta) - Fx. Pudjo Wibowo (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this paper is to determine the effect of compensation and motivation on the performance of employees of PT Indoraya International. The research was done by spreading the quaterner, while the research method using Simple Random Sampling.The t test shows that the magnitude of t for compensation (X1) is 2.843 and the value of t arithmetic for motivation (X2) is 2,373. all of which show larger than t table is 1,984. so the hypothesis that states compensation and motivation have a positive effect partially on employee performance at Company PT Indoraya International, F test, F calculated> F table or 25.984> 2.70 or signification level (sig) 0.000 <0.05 so that the hypothesis that states compensation and work motivation together affect the employee's performance at CompanyPT Indoraya International and coefficient of determination indicate that compensation and work motivation contributed 37.7% to Employee Performance at PT.Indoraya International.